Caribbean Report 08-01-1997 - Orr, Carol (anchor); Hughes, Hubert (interviewee); Smith, Colin (interviewee); Pastor, Robert (interviewee); Henry, Fitzroy (interviewee); Simon, John (The British Broadcasting Corporation, 1997)
Britain’s Foreign and Commonwealth Office is defending the controversial reserve powers of the governors of its five dependent territories in the Caribbean. Anguilla’s Chief Minister Hubert Hughes strongly criticises the government in what he says are plans to increase those power. An FCA spokesman also discusses the constitutional aspect of it and gives Britain’s present position. The next segment discusses the introduction of VAT in Barbados and its effects. Industrial unrest in Guyana among public sector workers is highlighted and Colin Smith reports on the issue. Former US President Jimmy Carter heads to several Latin American countries as well as Jamaica to discuss matters of free trade and drug trafficking. Dr Robert Pastor, Programme Director of the Carter Centre, gives his view on the matter. The final segment reports that manufacturers of several brands of powdered milk are breaking internationally agreed rules on how to market their products. Warren Gordon, John Simon of Save the Children and Fitzroy Henry of Caribbean Food and Nutrition Institute in Jamaica deal with the issue of powdered milk being portrayed as an ideal substitute for breast milk.
1. Headlines (00:00-00:26)
2. Britain defends the reserve powers for governors of independent territories (00:30-04:54)
3. The week after the introduction of VAT, Barbadians are complaining bitterly about hefty price rises (04:55-6:58)
4. Four unions in Guyana order a work to rule for back dated pay (07:00-8:39)
Keywords: Commonwealth countries.; Value-added tax -- Barbados.; Strikes and lockouts -- Guyana.; Presidential visit.; Infant formulas.; Labor unions-- Guyana.; Free trade -- Caribbean.; Drug traffic -- Caribbean Area.; Carter, Jimmy, 1924-; Public sector workers -- Guyana.; Unions -- Guyana.; Industrial relations -- Guyana.; Baby powdered milk.; Breast milk.; Caribbean Food and Nutrition Institute.; Argentina -- Presidential visit.; Brazil -- Presidential visit.; Chile -- Presidential visit.; Jamaica -- Presidential visit.